2013
DOI: 10.1017/s1751731113001754
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical approaches to detect low concentrations in progesterone profiles

Abstract: There is a general need for higher objectivity and accuracy in describing the physiological fertility performance of dairy cows. To develop the alternative meaningful starting points for the selection of genetically superior dairy cows, this study focused on the detection of low progesterone concentrations, which are indicative of estrus events. Three mathematical approaches were used: one based on the exponentially weighted moving average control chart, and two threshold methods, which were developed in-house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…First luteal activity was determined by the first postpartum progesterone value above the threshold value of 0.8 ng of progesterone/ mL of skim milk, preceded by low progesterone. The threshold (0.8 ng/mL) for identifying the presence of luteal activity was chosen based on a preliminary study (von Leesen et al, 2013).…”
Section: Characterization Of Luteal Activity Based On Progesterone Pr...mentioning
confidence: 99%
“…First luteal activity was determined by the first postpartum progesterone value above the threshold value of 0.8 ng of progesterone/ mL of skim milk, preceded by low progesterone. The threshold (0.8 ng/mL) for identifying the presence of luteal activity was chosen based on a preliminary study (von Leesen et al, 2013).…”
Section: Characterization Of Luteal Activity Based On Progesterone Pr...mentioning
confidence: 99%
“…For milk P4 to be useful as an indicator for fertility events, the raw P4 measurements should be converted into specific information, or even better, actions to be taken by the herdsmen on farm. In this context, it is shown that both the variability of the measurements and the variability between estrous cycles should be taken into account (Friggens and Chagunda, 2005;Friggens et al, 2008;von Leesen et al, 2013). In general, this means that the monitoring algorithm should meet following requirements: (1) it should be robust against outliers and different levels of measurement errors, which might be dependent on the measurement and calibration technique (Adriaens et al, 2017); (2) it should be able to discriminate between luteal and follicular concentrations to indicate actions such as insemination, embryonic loss, and possible cyst in an individualized way; and (3) it should be automated and implementable on farm.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, for milk P4 to be useful as an indicator for fertility events, the raw P4 measurements should be converted into specific information, or even better, ‘actions’ for the farmer. In this context, it is shown that both the variability of the measurements and the variability between estrous cycles should be taken into account (Friggens and Chagunda, 2005; Friggens et al, 2008; von Leesen et al, 2013). In general, this means that the monitoring algorithm should meet following requirements: (1) it should be robust against outliers and different levels of measurement errors; (2) it should be able to discriminate between luteal and follicular concentrations to indicate actions such as ‘inseminate’, ‘embryonic loss’, ‘cyst possible’ in an individualized way and (3) it should be automated and implementable on-line.…”
Section: Introductionmentioning
confidence: 99%